2020
DOI: 10.1002/pol.20200435
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐growth polycondensation via the substituent effect: Investigation of the monomer structure on synthesis of poly(N‐octyl‐benzamide)

Abstract: A systematic study of the behavior of different leaving groups on a variety of ester‐based monomers was performed for the chain‐growth polycondensation synthesis of poly(N‐octyl benzamide). Linear and branched alkane esters were compared with their phenyl analogs using both computational and experimental methods. Kinetic experiments along with qualitative solubility observations were used, with the aid of nuclear magnetic resonance spectroscopy and gel‐permeation chromatography, to determine progress of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 42 publications
(76 reference statements)
1
23
0
Order By: Relevance
“…[20] In an effort to better understand the effect of monomer structure on the kinetics of the CGC process and on the polymers produced, we recently investigated the polymerization of a variety of N-octyl benzamidebased monomers with different ester substituents. [8] The main conclusion from this work was that the structure of the monomers ester-leaving group dictates the reactivity of the monomer in CGC and the solubility of the polymerization by-products. One of the most interesting observations from this previous study was that, while the phenyl ester monomers demonstrated faster reactivity and increased solubility of the lithium phenoxide byproducts, they were also more difficult to control during polymerization, which resulted in broader molecular weight distributions and multimodal GPC traces.…”
Section: Computation Modeling Parametersmentioning
confidence: 91%
See 4 more Smart Citations
“…[20] In an effort to better understand the effect of monomer structure on the kinetics of the CGC process and on the polymers produced, we recently investigated the polymerization of a variety of N-octyl benzamidebased monomers with different ester substituents. [8] The main conclusion from this work was that the structure of the monomers ester-leaving group dictates the reactivity of the monomer in CGC and the solubility of the polymerization by-products. One of the most interesting observations from this previous study was that, while the phenyl ester monomers demonstrated faster reactivity and increased solubility of the lithium phenoxide byproducts, they were also more difficult to control during polymerization, which resulted in broader molecular weight distributions and multimodal GPC traces.…”
Section: Computation Modeling Parametersmentioning
confidence: 91%
“…The methyl ester monomer M-OAB was chosen as a control, since it has been extensively used in previous studies. [8,18,[20][21][22][23][24] The polymerization of M-OAB with no initiator and 1 M equivalent of LiHMDS yielded no measurable polymer formation over a 12 hr period at either 0 or −20 C, indicating that, at these temperatures, self-initiation is not present for the commonly used M-OAB monomer. However, our previous studies have demonstrated that the methyl ester monomer has low reactivity at these temperatures, even in the presence of initiator, due to the basicity of the methoxide-leaving group.…”
Section: Effect Of No Initiator and Different Molar Equivalent Of Lmentioning
confidence: 99%
See 3 more Smart Citations